OCOD-CTTP integrated science: School based assessment marker/tutor handbook (Organization for Cooperation in Overseas Development)
This manual informs tutors/evaluators and students about the Caribbean Examinations Council's (CXC) School-Based Assessment (SBA) of integrated science skills. It includes directions for the teacher/evaluator and a student activity package. The SBA is done in agricultural science, biology, chemistry, integrated science, and social studies, and is designed to give teachers a greater role in the assessment of their students and to widen the range of abilities assessed. The evaluator's handbook describes the purpose and nature of SBA and outlines, in detail, the skills assessed--manipulation, observation, recording, interpretation, cooperation, and persistence. There is also a discussion of assessment timing (conducted four times in each of the last two years of secondary school), rating guidelines, procedures for conducting the assessment, recording the scores, the use of laboratory notebooks, and suggested activities. The Learner Activity Package includes an introduction to the SBA, a discussion of what scientists do, and a review of the six practical skills that the SBA looks for. The balance of the manual contains instructions for 32 assessment activities
Keywords: Comprehensive Teacher Training Programme